PENDIDIKAN ETIKA DAN MORAL MEMBANGUN SUMBER DAYA MANUSIA MENGHADAPI KEMAJUAN TEKNOLOGI - Dia Ruslaini (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Understanding moral education is a planned undertaking to change attitudes, behaviors, actions, behaviors undertaken by learners in order to be able to interact with the community environment in accordance with the moral and cultural values of local communities. In general, the scope of moral education is the cultivation and development of values, attitudes and behaviors according to noble character values. Among the values that need to be inculcated is polite, disciplined, hearted, soft-hearted, faithful and cautious, strong-willed, modest, responsible, tolerant, honest, independent, humane, introspective, loving knowledge, others, compassion, shame, self-confidence, willing to sacrifice, humble. with the inclusion of ethics and morals at every level of education will ensure that all learners will become human resources ready to face technological advances in this era of globalization and educators are also more convinced that the next generation of the nation as these learners can be used as a foundation for advancing the nation because they are equipped with strong ethics and morals and make them know to behave in accordance with the social values and values of life that exist. Keywords— Ethics and Moral Education, Human Resources, Technological Advancement